2000
DOI: 10.1055/s-2000-7393
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Bleeding Due to Worm Infestation, with Negative Upper Gastrointestinal Endoscopy Findings: Impact of Enteroscopy

Abstract: In developing countries, worm infestation should be considered an important cause of obscure acute gastrointestinal bleeding. Evaluation of the jejunum using an enteroscope will result in more frequent diagnosis of worms as a cause of acute gastrointestinal bleeding which might have been classified as obscure gastrointestinal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
2
18
0
1
Order By: Relevance
“…The authors reported multiple rounded or oval erosions with 2–4 mm in size, with presence of fresh blood, oozing from erosions [9]. Lesions were also observed in our cases.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The authors reported multiple rounded or oval erosions with 2–4 mm in size, with presence of fresh blood, oozing from erosions [9]. Lesions were also observed in our cases.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, the first description of massive jejunal bleeding by ascariasis was performed during enteroscopy investigation [9]. The authors reported multiple rounded or oval erosions with 2–4 mm in size, with presence of fresh blood, oozing from erosions [9].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hookworm infestation caused overt OGIB in six of the seven patients, two of whom had massive bleeding. Small series and case reports on hookworm infestation causing OGIB have been reported from India on enteroscopy 29–31 . Small bowel tuberculosis was seen in three patients in our series.…”
Section: Discussionsupporting
confidence: 45%
“…Small series and case reports on hookworm infestation causing OGIB have been reported from India on enteroscopy. [29][30][31] Small bowel tuberculosis was seen in three patients in our series. The CE findings of small bowel tuberculosis have been reported elsewhere as case reports or small series, 32,33 and our study also confirms these findings.…”
Section: Discussionmentioning
confidence: 52%
“…59 Outcomes studies of the value of push enteroscopy in non-bleeding conditions suggest that it can be of value in malabsorption, 14 60 Crohn's disease, 61 non-steroidal anti-inflammatory drug toxicity, 62 and worm infestation. 63 It can be usefully performed in non-specialist district general hospitals. 64 It may be helpful to have some knowledge of the clinical patterns and appearances of the many less common or rare diseases which can affect the small intestine.…”
Section: Complicationsmentioning
confidence: 99%